Development Process of Topology Optimized Casted Components - Kåmark, Nadine (My University, 2018)
Both weight optimization and casting as a manufacturing method is widely used in the industry today. Topology optimization, as a weight optimization approach, is used to design lighter and more competitive components. Meanwhile, casting is a time and cost-efficient manufacturing method with the capacity to create complex shapes. Today, castability is not taken into account until the end of the development process. When the design is adjusted to become feasible to cast, mass is added which does not necessarily contribute to improve the structural strength. Thus, the structure is no longer optimized. Casting simulations assist in evaluating castability, but generally require animations and pictures to be analyzed manually. At Volvo Cars and within the Re-OPTIC project founded via LIGHTer, there is an interest in finding methods to evaluate castability in the early phase of the development process. The purpose of this thesis is therefore to find a way of evaluating castability numerically, in order to be able to compare design concepts in the early phase of the development process. A process where optimization results can be casting-simulated, without manually realizing the design using CAD, is also presented in this thesis. Furthermore, the topology optimization manufacturing constraints member size control and draw direction are evaluated from a weight perspective, as well as a discretization improvement tool and the usage of two design spaces. This thesis is only considering the casting solidification process. The topology optimization work is carried out in the commercial software OptiStruct. The casting simulations is obtained using the commercial software Click2Cast.
Keywords: Materialvetenskap; Transport; Maskinteknik; Teknisk mekanik; Fastkroppsmekanik; Materials Science; Transport; Mechanical Engineering; Applied Mechanics; Solid mechanics